The process of investigation concepts and strategies for investigators in the private sector - Sennewald, Charles A., 1931-; Tsukayama, John K. (Amsterdam : Butterworth-Heinemann, 2014)
The Process of Investigation, Fourth Edition addresses the needs of today's private sector investigative professional by providing a full-spectrum treatment of the investigative process, from case inception and investigative strategy selection to executing complex investigative techniques, to creating reports useful for corporate, legal, and prosecutorial purposes. Continuing in the tradition of its previous editions, The Process of Investigation, Fourth Edition covers essential topics overlooked in books on the public aspects of investigation. Investigative skills such as surveillance techniques, interviewing and interrogation, collecting and documenting evidence, and taking confessions and written statements are all discussed, and supplemented with updated case studies and examples from the authors' own professional experiences.
Chapter 13 -- the use of informants.
Includes bibliographical references at the end of each chapters and index.
CIP data; resource not viewed.
Elsevier
Keywords: Criminal investigation; Private investigators; Private security services; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Criminal investigation; Private investigators; Private security services; Electronic books; Electronic books